2012
DOI: 10.5194/acp-12-11213-2012
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of nitrate, sulfate, and ammonium aerosols over the United States

Abstract: Abstract. Atmospheric concentrations of inorganic gases and aerosols (nitrate, sulfate, and ammonium) are simulated for 2009 over the United States using the chemical transport model GEOS-Chem. Predicted aerosol concentrations are compared with surface-level measurement data from the Interagency Monitoring of Protected Visual Environments (IMPROVE), the Clean Air Status and Trends Network (CASTNET), and the California Air Resources Board (CARB). Sulfate predictions nationwide are in reasonably good agreement w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 36 publications
7
101
0
Order By: Relevance
“…Heald et al (2012) used IASI observations along with the GEOS-Chem chemical transport model to show that NH 3 is likely underestimated in California, leading to a local underestimate of ammonium nitrate aerosol. At the same time, Walker et al (2012) using TES observations showed a similar under-prediction of ammonia emissions by GEOS-Chem over California, which has among the largest concentrations of ammonia in the USA. TES satellite and in situ observations were also used to evaluate the new treatment of ammonia bidirectional fluxes in the CMAQ and GEOS-Chem models .…”
Section: Introductionmentioning
confidence: 62%
“…Heald et al (2012) used IASI observations along with the GEOS-Chem chemical transport model to show that NH 3 is likely underestimated in California, leading to a local underestimate of ammonium nitrate aerosol. At the same time, Walker et al (2012) using TES observations showed a similar under-prediction of ammonia emissions by GEOS-Chem over California, which has among the largest concentrations of ammonia in the USA. TES satellite and in situ observations were also used to evaluate the new treatment of ammonia bidirectional fluxes in the CMAQ and GEOS-Chem models .…”
Section: Introductionmentioning
confidence: 62%
“…This consistent behavior suggests that the specific model is not the cause of the sulfate underprediction. A global model study that included ocean dimethyl sulfide (DMS) emissions showed a better sulfate performance in California (Walker et al, 2012). Therefore, missing emissions sources such as the sulfur emitted as DMS from the Pacific Ocean likely contribute to the sulfate underpredictions in the current study.…”
Section: Statistical Evaluationmentioning
confidence: 97%
“…comparisons between measured emissions and concentrations with model inventories found significant discrepancies (Heald et al, 2012;Nowak et al, 2012;Walker et al, 2012).…”
Section: J Miller Et Al: Open-path Qcl-based Ammonia Sensormentioning
confidence: 99%